Empleo de biomarcadores para evaluar el proceso de daño en ostión Crassostrea virginica y su respuesta ambiental - Guzmán García, Xochitl (Universidad Autónoma Metropolitana, 2007)
The presence of pollutants, such as toxic metals, is affecting the tissues of the oyster from the Mandinga Lagoon, State of Veracruz, Mexico. The objective of this study was to assess, with biomarkers, the effects of exposure to metals (Cr, Cd y Pb) on the oyster Crassostrea virginica in the cited lagoon; after a depuration process in the laboratory and during a cadmium intoxication depuration bioassay. Samples of water, sediment, and oysters were collected in March, June, and October 2003 and in January and May 2004. In the laboratory, the oysters were kept in aquariums with metals free water for 21 days sampling every 72 h. Oysters were exposed to 100 µg/l of cadmium for 72 h and depurated (for 24, 48, 72, 96, 120, 144, 168, 192, 216, and 230 h). Metal concentrations were determined in water, soil and oyster tissue in fresh and detoxified Crassostrea virginica by EAA. The biomarkers used were: condition index, histopathological responses as histochemistry and immunohistochemistry, and analysis of the electrophoretic pattern. Metal concentrations in the lagoon water were within the permissible limits established by Mexican legislation. The values in sediments correspond to those not producing biological effects (ERL) according to the limit proposed by Long et al., (1995). In the oysters, the highest concentrations corresponded to Pb and were above 5.84 μgg-1 dry weight (d.w.), Cd was recorded at average values of 2.23 μgg-1 d.w., and Cr values were above 6 μgg-1 d.w. The metal levels detected in oysters exceeded the maximum permissible limits (MPL) for Cd and Pb as established by Mexican legislation. Oysters were unable to eliminate the concentrations of bioaccumulated metals during the detoxification stage. Oysters exposed to cadmium in the laboratory did not eliminate the metal after 384 h. The histopathological analysis revealed lesions in the digestive gland, edema, and atrophy of epithelia in the digestive tubules, presence of brown vesicles, hemocytic reaction, and necrosis. During detoxification, a higher number of epithelia were observed in the tubules, as well as an increment in brown cell vesicles and hemocytic reaction. Statistically significant correlations were established between the concentration of contaminants in oyster tissues and the concentrations of Cd and Cr in sediments (r = 0.64 and 0.80, respectively). Forty seven percent of oysters presented histopathological lesions related with the metal concentrations. The electrophoretic pattern showed an increased of 70, 45 and 15 kDa proteins, this suggests the over expression of chaperone and metalotionein proteins. It is important to continue monitoring the biomarkers studied in this work and to detect the sources of pollution, as well as to evaluate the effects on the organisms to be able to select culture areas and establish adequate criteria for the exploitation of such an important fishery resource at the national level. Key works: Oyster, Crassostrea virginica, metals, histopathological; Los ostiones no fueron capaces de eliminar el metal bioacumulado a concentraciones menores del LMP durante la fase de desintoxicación; los expuestos a cadmio en el laboratorio tampoco eliminaron el metal después de 384 h. El análisis histopatológico reveló lesiones en la glándula digestiva; edema, atrofia de los epitelios en la luz de los túbulos del tracto digestivo, presencia de vesículas cafés, reacción hemocítica y necrosis. Durante la desintoxicación se observó mayor número de epitelios en los túbulos, e incremento de las vesículas cafés y de la reacción hemocítica. Relaciones estadísticamente significativas se establecieron entre la concentración de contaminantes en los tejidos de los ostiones con las concentraciones de cadmio y cromo determinadas en el sedimento (r = 0.64 y 0.80 respectivamente). Sobre el promedio, 47% de los ostiones presentaron lesiones histopatológicas que pueden relacionarse con las concentraciones de metales. El patrón electroforético demostró un incremento de proteínas con Mr de 70, 45 y 15 kDa que sugieren la sobre-expresión de proteínas chaperonas y metalotioneínas. Es importante continuar con el monitoreo con los biomarcadores estudiados en este trabajo, así como detectar las fuentes de contaminación y la evaluación de efectos en organismos a fin de que se cuente con criterios para la selección de áreas de cultivo, y la explotación de tan importante recurso pesquero a nivel nacional.